1984
DOI: 10.1071/ch9840537
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of polyhalogenated monoterpenes from Plocamium species

Abstract: Extraction of Plocamium mertensii and an unclassified Plocamium species found off the Western Australian coast yielded (1R,2S,4S,1'E)-2-bromo-1-chloro-4-(2'-chloroethenyl)-1-methyl-5-methylenecyclohexane(3) and (1R,2S,4R,5R,1'E)-4-bromo-1,2-dichloro-5-(2'-chloroethenyl)-1,5-dimethylcyclohexane (4) respectively. The structures and absolute configurations were established by single-crystal X-ray crystallographic structure determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…Metabolite 80 possesses unusual biological activity. Apart from weak cytostatic and antibacterial activity, it produces a spastic syndrome in mice which persists for several days but is however reversible (Norton et al, 1977;Capon et al, 1984).…”
Section: Plocamium Mertinsiimentioning
confidence: 98%
See 1 more Smart Citation
“…Metabolite 80 possesses unusual biological activity. Apart from weak cytostatic and antibacterial activity, it produces a spastic syndrome in mice which persists for several days but is however reversible (Norton et al, 1977;Capon et al, 1984).…”
Section: Plocamium Mertinsiimentioning
confidence: 98%
“…The metabolites were tested individually against the fungus Cladosporium cucumerinum on a TLC plate and were found to have moderate activity. From Crews et al, 1978;3 : Crews et al, 1977;4 : Mynderse et al, 1975;5 : Kazlauskas et al, 1976;6 : Mynderse and Faulkner 1978;7 : Crews et al, 1984b;8 : Barrow and Temple 1985. another unclassified Plocamium species found off the Western Australia coast metabolite 166 was isolated and identified on the basis of its spectral data ( Figure 17) (Capon et al, 1984).…”
Section: Plocamium Pacificummentioning
confidence: 99%
“…Plocamium cartilagineum is a species of red algae (family Plocamiaceae, order Gigartinales). This species is characterized by its interesting secondary metabolites, being a rich source of diverse polyhalogenated monoterpenes, with a surprising degree of halogen incorporation (Young et al, 2013; Inés et al, 2004, Palma et al, 2004, Gao et al, 2001, Norton et al, 1977; Capon et al, 1984; Wright et al, 1990; Mynderse and Faulkner, 1975). Polyhalogenated monoterpenes vary for the given species depending on collection, location and season (Fuller et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in 1982 demonstrated the antibacterial and cytostatic activities of 5, 6, 9 and 15 (González et al, 1982). In 1984 an unclassified Plocamium species collected off the Western Australian coast, led to the isolation of the cyclic monoterpene 22 and also revised the structure of mertensene to 24 from Capon et al (1984). Both 22 and mertensene (24) were characterised by spectroscopic techniques as well as by single X-ray crystallographic studies which defined their absolute configurations (Capon et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…A case in point is the structure of mertensene for which a total of five structures have been reported to date. These included mertensene reported as 11 , 25 , 24 (Capon et al, 1984), 26 (Crews et al, 1984) and finally 27 (Coll et al, 1988). Alternative strategies reported include, 13 C (or 1 H) T 1 measurements, but ambiguities have been noted with this method, as well as lanthanide-induced shift methods (Van Engen et al, 1978;Crews et al, 1984).…”
Section: Introductionmentioning
confidence: 99%